ALLEREGENIC ACTIVITY OF BOVINE DANDER EXTRACT - Sundus S.Baker (Basrah Journal of Veterinary Research)
This study was conducted in Basrah at period from March through July 2000 .The protein extract from Bovine dander was prepared with extraction followed by puriﬁcation and fractionation by gel filtration into tow peaks. Elisa inhibition with serum samples from 77 patients who were sensitive to bovine dander, revealed similar lgE,lgG binding patterns for each peak. Also, there is a cross —reaction . between these two peaks.PeakII exhibited the highest IgE binding inhibition and showed a specific allergenic activity about two fold higher than that of peakI.The allergenecity ofpuriﬁed allergen was not lost during purification process.